TANTANGAN DAN PELUANG ASURANSI SOSIAL SYARIAH DI INDONESIA (STUDY LITERASI JAMINAN KESEHATAN NASIONAL): Meutia Safrina Rachma Magister Ilmu Ekonomi Fakultas Bisnis dan Ekonomika Universitas Islam Indonesia meutiasafrina02@gmail.com - Rachma, Meutia (JURNAL AKUNTANSI DAN MANAJEMEN MADANI, 2024)
This study aims to determine the challenges and opportunities of the National Health Insurance seen from the level of sharia compliance, governance and strategies and opportunities that will be faced in the future. This research is qualitative and uses secondary data. The result obtained in this study are that the Social Health Insurance has met sharia compliance but with certain terms and conditions, JKN also still has some shortcomings that must be considered by the government so thai it is hoped that in the future JKN will be able to compete with other social security.